Examining associations between area-level spatial measures of housing with selected health and wellbeing behaviours and outcomes in an urban context. (January 2017) - Badland, Hannah; Foster, Sarah; Bentley, Rebecca; Higgs, Carl; Roberts, Rebecca; Pettit, Christopher; Giles-Corti, Billie
Abstract: Adequate and affordable housing is a major social determinant of health; yet no work has attempted to conceptually map and spatially test area-level measures of housing with selected health and wellbeing outcomes. Sourcing data from 7, 753 adults from Melbourne, Australia, we tested associations between area-level measures of housing density, tenure, and affordability with individual-level measures of neighbourhood safety, community satisfaction, and self-rated health. Compared with the reference groups, the odds of: feeling unsafe was higher for residents living in areas with less affordable housing; community dissatisfaction was ~30% higher in those living in areas with >36% residential properties assigned as rentals, and was significantly higher in the least affordable areas (OR =1.57). Compared with the reference groups, as dwelling density, proportion of rental properties, and housing unaffordability increased, the odds of reporting poorer self-rated health increased; however these associations did not always reach statistical significance. This work highlights the benefits of evidenced-based planning spatial measures to support health and wellbeing. Highlights: We mapped and tested spatial measures of housing with health and wellbeing. Housing density was positively associated with poorer self-rated health. Rental properties were positively associated with community dissatisfaction and poorer self-rated health. Unaffordable housing was positively associated with feeling unsafe, community dissatisfaction, and poorer self-rated health. Spatial measures of housing can be used to inform evidenced-based urban planning.